1991
DOI: 10.1111/j.1600-0749.1991.tb00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tumor Cell Invasion by Verapamil

Abstract: Verapamil, a calcium channel antagonist, inhibits murine B16 melanoma and colon adenocarcinoma C26 tumor metastasis by altering platelet aggregation [Tsuruo, T., et al. (1985) Cancer Chemother. Pharmacol., 14:30-33]. However, the role of calcium homeostasis in regulating several biochemical pathways implicated in other steps of the metastatic cascade suggests that calcium channel antagonists could also inhibit metastasis by other mechanisms. In this report, non-toxic doses of verapamil reversibly decreased hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…D-Verapamil has no undesired effects on calcium channels [15] and therefore may produce fewer side effects in vivo than the other available isomers. These results and the concentration range we used are in concordance with the inhibitory effects and concentration of the racemic verapamil isomer on proliferation, migration and contraction of several other cell types [5,9,28,43]. In addition to the inhibitory effect of verapamil on macrovascular human umbilical vein endothelial cells (HUVEC) by inducing cell cycle arrest in G0/G1 phase [44], all verapamil isomers inhibit the proliferation of microvascular CECs.…”
Section: Discussionsupporting
confidence: 67%
“…D-Verapamil has no undesired effects on calcium channels [15] and therefore may produce fewer side effects in vivo than the other available isomers. These results and the concentration range we used are in concordance with the inhibitory effects and concentration of the racemic verapamil isomer on proliferation, migration and contraction of several other cell types [5,9,28,43]. In addition to the inhibitory effect of verapamil on macrovascular human umbilical vein endothelial cells (HUVEC) by inducing cell cycle arrest in G0/G1 phase [44], all verapamil isomers inhibit the proliferation of microvascular CECs.…”
Section: Discussionsupporting
confidence: 67%
“…In particular, verapamil decreased FSH-and LH-induced migration in OV207 cells and proliferation in both cell lines. Verapamil has also been shown to reduce cancer cell migration in murine mammary carcinoma and human melanoma cell lines (Yohem et al 1991, Todaro et al 2003. In a phase II trial, the cytostatic inhibitor of calcium influx carboxyamidotriazole has been shown to stabilise some patients with EOC who had relapsed for between 6 and 13 months (Hussain et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This drug inhibits A2058 human melanoma and OVCAR ovarian carcinoma primary tumor growth and has recently been reported to have effects on calcium channels [62]. We recently showed that various calcium channel blockers, including verapamil, inhibit tumor cell invasion and metastasis [63]. Similarly, Cresson et al developed BABIM (bis-(5-amidino-2-benzimidazolyl-methane)) as a nontoxic inhibitor of trypsin, urokinase, and plasmin [64].…”
Section: Discussionmentioning
confidence: 99%